An under-recognised cause of spastic paraparesis in middle-aged women. Issue 3 (23rd October 2013) - Bargiela, D; Eglon, G; Horvath, R; Chinnery, P F
Abstract : Having excluded common structural, inflammatory and vascular causes of a spastic paraparesis, the diagnostic yield of further clinical investigations is low. Here, we show that testing for rare metabolic and genetic causes can have important implications for both the patient and their family.